Eric Carle´s Picture Books in ELT - Mikulová, Jana (Univerzita Pardubice, 2014)
This master thesis focuses on the picture books by Eric Carle and their possible use in English language teaching. The theoretical part explores picture books in the context of children’s literature and presents the method of storytelling as a suitable tool for suing literature in English language teaching. Furthermore, the thesis defines a term curriculum in the Czech context and introduces principles and rules for the development of curricular documents. The practical part analyses the School educational programme of a chosen school and presents the thematic plan and lesson plans designed for a target group of learners. The thematic plan and lesson plans integrate one picture book by Eric Carle.
Využití obrázkových knih Erica Carla ve výuce anglického jazyka
Keywords: dětská literatura; Eric Carle; obrázkové knihy; metoda vyprávění příběhů; žáci prvního stupně základní školy; výuka anglického jazyka; children’s literature; picture story books; storytelling; young learners; English language teaching